Death and dying from the perspective of multiprofessional residents in a teaching hospital - Tietbohl, Daniel (2017)
This study aimed to analyze and describe the understanding of multi-professional residents of a teaching hospital regarding death and dying. A qualitative study was performed using Bardin subject analysis. A semistructured interview was used for the collection of data, which was analyzed with QSR NVivo 11 software. Itwas noted that the interviewees believe that working with the theme of death and dying is entirely pertinent, and that it is an indispensable subject in academic training for integral care. It was found that the interviewees did not feel they were prepared to deal with the process of death and dying.